2022
DOI: 10.3389/fmicb.2022.870816
|View full text |Cite
|
Sign up to set email alerts
|

EBV Exploits RNA m6A Modification to Promote Cell Survival and Progeny Virus Production During Lytic Cycle

Abstract: N6-methyladenosine (m6A) mediates various biological processes by affecting RNA stability, splicing, and translational efficiency. The roles of m6A modification in Epstein-Barr virus (EBV) infection in the lytic phase are unclear. Here, knockout of the m6A methyltransferase, N6-methyladenosine methyltransferase-like 3 (METTL3), or inhibition of methylation by DAA or UZH1a decreased the expression of viral lytic proteins and reduced progeny virion production. Interestingly, cell growth and viability were decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The proteins encoded by the m 6 A peaks of the PRV transcripts were involved in nearly every progression of the PRV life cycle, such as viral entry and intercellular diffusion (Pomeranz et al, 2005), DNA replication, repair and recombination (Ben-Porat et al, 1983), assembly of viral particles (Kopp et al, 2002), viral nuclear export (Wagenaar et al, 1995), capsid assembly and maturation (Pomeranz et al, 2005), among others. Similar to EBV (Xia et al, 2021;Yanagi et al, 2022) and KSHV (Baquero-Perez et al, 2019), which belonged to the Herpesviridae family, the majority of m 6 A peaks were distributed on the CDS of viral mRNAs, especially the 3′ end, suggesting that m 6 A modification might regulate viral gene transcription or translation and play a role in viral assembly and replication.…”
Section: Discussionmentioning
confidence: 97%
“…The proteins encoded by the m 6 A peaks of the PRV transcripts were involved in nearly every progression of the PRV life cycle, such as viral entry and intercellular diffusion (Pomeranz et al, 2005), DNA replication, repair and recombination (Ben-Porat et al, 1983), assembly of viral particles (Kopp et al, 2002), viral nuclear export (Wagenaar et al, 1995), capsid assembly and maturation (Pomeranz et al, 2005), among others. Similar to EBV (Xia et al, 2021;Yanagi et al, 2022) and KSHV (Baquero-Perez et al, 2019), which belonged to the Herpesviridae family, the majority of m 6 A peaks were distributed on the CDS of viral mRNAs, especially the 3′ end, suggesting that m 6 A modification might regulate viral gene transcription or translation and play a role in viral assembly and replication.…”
Section: Discussionmentioning
confidence: 97%
“…HEK293T and HEK293T/EBV cells were grown in DMEM (Sigma-Aldrich, St. Louis, MO, USA) supplemented with 10% FBS. Akata(-) cells, Akata/EBV-EGFP [ 53 ], and LCLs established by recombinant EBV infection were maintained in RPMI 1640 supplemented with 10%-15% FBS. AGS/EBV-EGFP cells (kindly gifted by Hironori Yoshiyama) [ 54 ] were grown in RPMI 1640 medium containing 10% FBS and 750 μg/mL G418 [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Treatment for tumors generally comprises surgery, hormonal therapy, Chemo/Target therapy, immunotherapy, radiotherapy, viruses/bacteria ( Yanagi et al, 2022 ), and more recently personalized therapy ( Beck et al, 2021 ; Inoue et al, 2021 ). The first-line treatment for low-grade hormone receptor-positive metastatic endometrial cancer includes platinum-based chemotherapy and hormonal therapy, and there is no standard follow-up treatment.…”
Section: Therapeutic Precismentioning
confidence: 99%
“…Apart from surgery, hormonal therapy, and radiotherapy, we introduced Chemo/Target therapy and immunotherapy associated with m6A. Above all, we collected the small molecule inhibitors that targeted m6A related proteins, which included ( Figure 3 ): 1 m6A modification, which could be inhibited by neplanocin A (NPC), Cycloleucine, and 3-Deazaadenosine ( Cayir, 2022 ); 2 METTL3, which was effectively repressed by STM2457 ( Yankova et al, 2021 ) and UZH1a ( Yanagi et al, 2022 ); 3 S-Adenosylhomocysteine (SAH), Antiviral agent 23/24 and STM2120 ( Yankova et al, 2021 ) was identified to inhibit the activity of METTL3/14 complex; 4 FB23 ( Huang et al, 2019 ), Rhein, Meclofenamic acid (MA) ( Huang et al, 2015 ), and Entacapone sodium salt could effectively repress FTO; 5 ALKBH5, whose potential inhibitor was IOX1 ( Li et al, 2016 ); 6 DC-Y3 and DC-Y13-27 were for YTHDF2 ( Wang et al, 2023 ); 7 SND1 was corresponding to Thymidine 3′,5′-disphosphate ( Jariwala et al, 2017 ); 8 IGF2BP2, which was restrained by CWI1-2 ( Weng et al, 2022 ); 9 MSI2, whose inhibitor was Romidepsin (FK228) ( Cayir, 2022 ; Zhu et al, 2022 ). …”
Section: Therapeutic Precismentioning
confidence: 99%
See 1 more Smart Citation